Contamination and current practice in decontamination of nebulisers in ventilated patients - Van Heerden, Lizl (My University, 2015)
Aerosol therapy is an important and frequently used method of delivering drugs to the patient on mechanical ventilation (MV). Different types of aerosol devices are available to deliver drug therapy during MV. These devices need to be used according to the manufacturer’s guidelines which include methods for decontamination and application. The methods used to store these nebulisers and the pathogens in the surrounding air may contribute to the contamination of these devices. Nebulisers have been identified as a possible source of ventilator-associated pneumonia (VAP). The incidence of contamination of nebulisers associated with current decontamination and storage protocols will lay the foundation for the development of evidence based practice of aerosol therapy in MV. Objectives The aim of this study was to determine the current incidence of contamination of nebulisers used within a ventilator circuit and surrounding air in the intensive care units (ICUs) of hospitals in Pretoria and to determine the current practice regarding decontamination and storage of these devices. Micro-organisms that colonise these contaminated nebulisers and the surrounding air were also identified. Methods A cross-sectional observational analytical study was done in seven ICUs in Pretoria whereby 61 nebulisers and the surrounding air were sampled and assessed. The unit manager of each ICU was asked questions to identify the current decontamination and storage protocols for nebulisers used within a ventilator circuit. Swabs were taken from the chambers of nebulisers used within a ventilator circuit and streaked on blood agar plates (BAPs). An air sampler was used to collect air samples from the surrounding environment. The BAPs of nebulisers and air were incubated for possible bacterial and fungal contamination. Species of the most recurrent colonies observed were identified in both air and nebuliser samples. Results A total of 61 nebulisers were sampled including 37 Micro Mist nebulisers and 24 Aeroneb nebulisers. The incidence of contamination found in the Micro Mist nebulisers were 51.4% (n=19) and the Aeroneb nebulisers were 50% (n=12). Most of the Aeroneb nebulisers in the ventilator circuit were wet which resulted in 50% bacterial contamination. All the ICUs in the hospitals in Pretoria had decontamination and storage protocols for the Micro Mist nebuliser. These protocols differed between ICUs and ICUs within the same hospital. Staff adherence to these protocols was low as the methods observed for storage and decontamination differed from the protocols stated to be used in the ICUs. Contamination rate was the least when the Micro Mist nebuliser was rinsed with alcohol and left open to the environment. Micro Mist nebulisers that were taken apart and left to dry under a sterile cloth resulted in the most fungal and bacterial contamination. No contamination was found in Micro Mist nebulisers that were used for Bisolvon aerosolisation. Coagulase-negative Staphylococcus species (spp.) was mostly found in air and Aeroneb samples and Enterococcus spp. mostly in the Micro Mist nebuliser. Both of these micro-organisms are common causes of VAP. Conclusion Both types of nebulisers presented with similar rates of contamination. Although the ICUs in the hospitals had decontamination and storage protocols in place, the incidence of contamination in the Micro Mist nebulisers was high. The rate of contamination in the Micro Mist nebulisers can be associated with different decontamination and storage protocols. This is the first study to identify the rate of contamination in the Aeroneb nebuliser. Most of the Aeroneb nebulisers were wet during the time of MV which increased the possibility of contamination. The micro-organisms found in nebulisers and air samples harbour pathogens that can cause VAP.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Science (Physiotherapy) Johannesburg, 2015